Moving on the trajectory : a qualitative study of new immigrants' acculturation in Finland - Huang, Judy (2015)
With a steady growth of immigration in Finland, the current number of immigrants has reached nearly 6% of the total population. These immigrants have crossed cultural boundaries for a new home and better life in Finland, but often face the compound challenges of navigating a new culture while striving to function efficiently in an unfamiliar environment. Thus, the aim of this study is to investigate new immigrants’ acculturation in Finland. Previous studies have been focused on either refugees or returnees, so this study aims to produce an inclusive investigation of acculturation of on both forced and voluntary immigrants, as well as returnees who have engaged in the official integration plan in Finland. A total of eleven new immigrants were interviewed face-to face. The interview questions explored the general status of the immigrants prior to migration, their adjustment and adaptation in the host society, acculturative stress, the preference of acculturation strategy, and transformation reported through their individual experience and interaction with the host population during the initial phase of the migration process. The results of this study identified the acculturative stressors as Finnish language deficiency, employment, and dealing with the medical system. Discrimination was not considered as a significant issue. The preferred acculturation strategy was integration strategy among the participants. In the associated matter of the individual’s cultural identity, the original background and nationality were the most important factor. The individuals’ transformations of cultural schemas were modified depending on the cultural context, individual background, and societal characteristics.